Investigation of Peripheral Effects of Citrus Limon Essential Oil on Somatic Pain in Male Wistar Rats: Role of Histaminergic System - Ali Mojtahedin (Journal of Advanced Biomedical Sciences, 2016)
Background & Objective: One of the plants used in traditional medicine is lemon which has analgesic effect. However, little research has been performed on the analgesic effect of lemon and mechanisms of action with an emphasis on neurotransmitters systems. Therefore, the present study set to investigate the peripheral effects of lemon essential oil on somatic pain using formalin test with an emphasis on histaminergic system in male Wistar rats.